Konsep Manajemen Harta dalam Perspektif Hadis - Ahmad Farikhin; Muhammad Najib; Rosihon Anwar; Heni Mulyasari (Diroyah : Jurnal Studi Ilmu Hadis, 2022)
Wealth is a facility given by Allah Subhanahu Wa Ta'ala to human beings to carry out their functions as leaders and managers of the earth where they live. In order to achieve happiness living in the natural world and the hereafter, Creator provides instructions to get excellent and correct treasures and how to use them. In this paper, the author describes The Concept of Asset Management from the Perspective of Hadith. This writing uses descriptive quantitative methods in the form of library research. The study results show that wealth will provide worldly benefits by means of reasonable consumption according to sharia guidelines, not doing israf and tabdzir on the one hand and not being stingy on the other. A good Muslim must be moderate israf, tabdzir and miserly so that his wealth positively impacts life both during life in this world and in the hereafter. If spent according to sharia guidelines, assets can be taken to death. The portion of the property consumed to meet worldly needs has an impact on worldly happiness, and the portion that is donated for the benefit of helping others will have a positive impact on its owner in the hereafter